Proportional-Integral Ammonium-based Aeration Control for Activated Sludge Process - Husin, M. H.; Rahmat, M. F.; Wahab, N. A.; Sabri, M. F. M.; Suhaili, S. (IEEE, 2020)
Most of the earlier research working on the aeration control of the activated sludge process (ASP) utilized the fixed dissolved oxygen (DO) concentration control strategy. This strategy typically works at elevated level of aeration to avoid nitrification failure and to meet biological oxygen demand (BOD) removal. The problem of elevated aeration is increased cost of aeration, which contribute the most to the total operation cost of wastewater treatment plant (WWTP). Some attempts have been made to solve this problem by utilizing aeration control that has a variation of the DO concentration using ammonium-based aeration control (ABAC) control strategy. The existing controller used is Proportional Integral (PI) controller, which the control gain is fixed. In this study, an adaptive feedback PI-ABAC is proposed using rule-based control technique. The performance assessment of the proposed controller was investigated by simulation using Benchmark Simulation Model No. 1 (BSM1) and the outcomes are compared with the static-gain benchmark-PI strategy. The proposed controller demonstrated better performance and as well as improved efficiency of nitrogen removal by 5.04%, reduced aeration energy by 1.51%, and reduced overall cost index by 0.30% when compared to static-gain benchmark PI controller.